2011
DOI: 10.1620/tjem.224.287
|View full text |Cite
|
Sign up to set email alerts
|

Association of Women's Birth Weight with Their Blood Pressure during Pregnancy and with the Body Size of Their Babies

Abstract: The women's own intrauterine environment may influence their own pregnancy and their babies. The aim of our study was to investigate how a woman's birth weight affects the course of her pregnancy later in life as well as the body size of her babies; this study was based on the developmental origins of health and disease (DOHaD) concept. We collected Maternal and Child Health handbooks from 414 women and their biological mothers. They were classified into 3 categories based on the Fetal growth curve of Japan: l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Twenty-eight papers were obtained: 3 review articles, 4 - 6 17 original articles, 7 - 23 2 brief reports, 24 , 25 2 letters, 26 , 27 1 research note, 28 and 3 proceedings 29 - 31 (see Table 1 ). Additionally, all the articles were in English, and all the proceedings were from an international conference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-eight papers were obtained: 3 review articles, 4 - 6 17 original articles, 7 - 23 2 brief reports, 24 , 25 2 letters, 26 , 27 1 research note, 28 and 3 proceedings 29 - 31 (see Table 1 ). Additionally, all the articles were in English, and all the proceedings were from an international conference.…”
Section: Resultsmentioning
confidence: 99%
“… 8 Future studies can evaluate the association between using 2 generations of birth weight recorded by the MCHH. 10 Thus, data from the MCHH may be used for assessing linkage similarities between generations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies and animal experiments have shown that nutritional disorders and environmental factors from the fetal period to infancy lead to not only morphological defects such as physical malformations, but also the occurrence of lifestyle-related diseases such as hypertension, diabetes mellitus, and cardiovascular events later in life (de Boo and Harding 2006;Rice et al 2006;Tanabe et al 2011). According to this evidence, the concept of developmental origins of health and disease (DOHaD) has been defined as the process through which the environment encountered before birth, or in infancy, shapes the long-term control of tissue physiology and homeostasis (Gluckman and Hanson 2004;Gluckman et al 2005).…”
Section: Introductionmentioning
confidence: 99%